Reinforcing gender stereotypes through legal Defence: the application of unjust provocation Defence in hate-motivated killings of LGBTQI in Turkey - Caltekin, Demet Asli (Crime, law and social change, 2022)
This article examines the gender implications of unjust provocation defence, which received little empirical attention than the theoretical. It focuses on the role of masculinity behind the application of unjust provocation defence in hate-motivated killings of LGBTQI in Turkey. By employing a qualitative content analysis to study four cases from Turkish domestic courts, it aims to provide an empirical background to the current theoretical debate on provocation defence. It argues that the non-recognition of hate crimes and the wide judicial discretion power of the courts jeopardise LGBTQI’s right to access the justice system, thus making them vulnerable to violence. Therefore, this article highlights the need to legislate hate crimes towards LGBTQI members to eliminate hostility towards them.